Profile of Implementation of Free Inquiry Learning Assisted By PhET and Critical Thinking Skills of Senior High School Students on Light Material - Rohmah, Anggi Aulidhia; Prahani, Binar Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This research was conducted to obtain a Free Inquiry Learning Implementation Profile assisted by PhET and Critical Thinking Skills of Senior High School Students on Light Material. The type of this research is descriptive preliminary research and does not test the hypothesis.Â The research subjects consisted of 111 students. Data collection techniques in a form of questionnaires, teacher interviews, and written tests which has been tested for validity and reliability. Then the data that has been obtained will be analyzed descriptively qualitatively. Based on the study results, findings in the form of 1) The ability of critical thinking skills of students in the low and medium category. The low category with a range of grades from 0 to 45 as many as 44 students where male 15 students, and 29 female students, the medium category with a range of grades from 46 to 75Â as many as 63 students where male 4 students and 59 female students, and high category with a range 75 to 100 as many as 4 female students; 2) Criteria for the lowest critical thinking skills is â€œevaluationâ€ with an average value of 1.00, 3) The implementation of the free inquiry model has the potential to improve studentâ€™s critical thinking skills. It can be concluded if the critical thinking skills possessed by students are low, so it is necessary to increase studentâ€™s critical thinking skills, namely by the implementation of free inquiry assisted by PhET.